Generalized Anxiety Disorder Sebagai Ide Penciptaan Seni Lukis. - Rudiana, Sarah Aulia; wiyono, Wiyono wiyono; hamzah, Amir Hamzah (Fenomen: Jurnal Fenomena Seni, 2023)
The creation of a work of art entitled Generalized Anxiety Disorder as an Idea for the Creation of Painting is a form of expression of the author in conveying what the author suffers and interest in the psychological world can be imagined into a work of painting. Mental health is often a little taboo for society to discuss. Generalized Anxiety Disorder is one of the mental health disorders that exist in the environment around us. Artists can use aspects of mental health as ideas in their work by representing the feelings and experiences experienced during the creation process. The embodiment of emotions as a visual form with certain symbols of the author with an antagoonist figurative, and the protagonist. Using acrylic techniques and media, the embodiment of feelings and feelings is expressed in a visually enjoyable work that highlights the two main characters, namely the antagonist and the protagonist